Promoter cis-element analyses reveal the function of αvpe in drought stress response of arabidopsis - Tang, Chu-Nie; Wan Abdullah, Wan Muhamad Asrul Nizam; Wee, Chien-Yeong; Balia Yusof, Zetty Norhana; Yap, Wai-Sum; Cheng, Wan-Hee; Baharum, Nadiya Akmal; Ong-Abdullah, Janna; Loh, Jiun-Yan; Lai, Kok-Song (MDPI, 2023)
Vacuolar processing enzyme (VPE) is a cysteine protease responsible for vacuolar proteins’ maturation and regulation of programmed cell death (PCD). Four isoforms of Arabidopsis thaliana VPEs were identified previously, but only the functions of βVPE, γVPE, and δVPE were determined. The specific function of a gene is linked to the cis-acting elements in the promoter region. A promoter analysis found repetitive drought-related cis-elements in αVPE, which highlight its potential involvement in drought regulation in A. thaliana. The further co-expression network portraying genes interacting with αVPE substantiated its drought-regulation-related function. Expression of αVPE was upregulated after drought treatment in A. thaliana. To confirm the role of αVPE, a loss of function study revealed that αVPE knockout mutants remained green compared with WT after drought treatment. The mutants had reduced proline activity, decreased sucrose content, and lower MDA content, but increased photosynthetic pigments, indicating that αVPE negatively regulates drought tolerance in A. thaliana. Taken together, our findings serve as important evidence of the involvement of αVPE in modulating drought tolerance in A. thaliana.